Seven years of aerosol scattering hygroscopic growth measurements from SGP: Factors influencing water uptake. Issue 17 (11th September 2017) - Jefferson, A.; Hageman, D.; Morrow, H.; Mei, F.; Watson, T.
Abstract: Long‐term measurements of changes in the aerosol scattering coefficient hygroscopic growth at the U.S. Department of Energy Southern Great Plains site provide information on the seasonal as well as size and chemical dependence of aerosol water uptake. Annual average sub‐10 μm fRH values (the ratio of aerosol scattering at 85%/40% relative humidity (RH)) were 1.78 and 1.99 for the gamma and kappa fit algorithms, respectively. The study found higher growth rates in the winter and spring seasons that correlated with a high aerosol nitrate mass fraction. fRH exhibited strong, but differing, correlations with the scattering Ångström exponent and backscatter fraction, two optical size‐dependent parameters. The aerosol organic mass fraction had a strong influence on fRH. Increases in the organic mass fraction and absorption Ångström exponent coincided with a decrease in fRH. Similarly, fRH declined with decreases in the aerosol single scatter albedo. Uncertainty analysis of the fit algorithms revealed high uncertainty at low scattering coefficients and increased uncertainty at high RH and fit parameters values. Key Points: Uncertainty in the calculated, RH‐dependent, aerosol scattering coefficient increased with ambient relative humidity and growth rate, and decreasing scattering coefficient for the two algorithms studied The aerosol hygroscopic growth at SGP exhibited a seasonal dependence, driven mostly by change in the aerosol chemical composition Correlations with the aerosol optical properties show that size‐related, aerosol organic composition regulates the aerosol uptake of water Plain Language Summary: Aerosol water content influences climate by enlarging particles that then scatter more sunlight and increase cloud droplet number. This study examines the effect of aerosol chemical composition and optical properties, that denote particle size and absorption, on aerosol water uptake. The paper's focus is on data from a continental site in north central Oklahoma that is part of the Department of Energy Atmospheric Radiation Measurement network. We found the aerosol water uptake to depend strongly on the aerosol inorganic content, size, and season.